2009
DOI: 10.1099/ijs.0.005413-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis and identification of Aeromonas species based on sequencing of the cpn60 universal target

Abstract: An analysis of the universal target (UT) sequence from the cpn60 gene was performed in order to evaluate its usefulness in phylogenetic and taxonomic studies and as an identification marker for the genus Aeromonas. Sequences of 555 bp, corresponding to the UT region, were obtained from a collection of 35 strains representing all of the species and subspecies of Aeromonas. From the analysis of these sequences, a range of divergence of 0-23.3 % was obtained, with a mean of 11.2±0.9 %. Comparative analyses betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 39 publications
4
33
0
1
Order By: Relevance
“…Previous studies based on the sequence analysis of several housekeeping genes have demonstrated that the AHC is not monophyletic (Soler et al, 2004;Küpfer et al, 2006;Saavedra et al, 2006;Nhung et al, 2007;Beaz-Hidalgo et al, 2009;Miñana-Galbis et al, 2009). Nevertheless, controversially, other studies have shown the monophylia of this group (Martínez-Murcia et al, 2005;Farfán et al, 2010).…”
Section: "Aeromonas Hydrophila Species Complex"mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies based on the sequence analysis of several housekeeping genes have demonstrated that the AHC is not monophyletic (Soler et al, 2004;Küpfer et al, 2006;Saavedra et al, 2006;Nhung et al, 2007;Beaz-Hidalgo et al, 2009;Miñana-Galbis et al, 2009). Nevertheless, controversially, other studies have shown the monophylia of this group (Martínez-Murcia et al, 2005;Farfán et al, 2010).…”
Section: "Aeromonas Hydrophila Species Complex"mentioning
confidence: 99%
“…Several attempts have been made to generate phylogenies using DNA gene sequences to reconstruct the correct genealogical ties among species in Aeromonas (Küpfer et al, 2006;Saavedra et al, 2006;Miñana-Galbis et al, 2009), but the genes chosen for this purpose are not always suitable and do not give congruent phylogenies (Farfán et al, 2010;Silver et al, 2011). Recently, two papers presenting MLST schemes for Aeromonas have been published (Martínez-Murcia et al, 2011;Martino et al, 2011) and there is an online MLST database of the genus Aeromonas, managed by Keith Jolley and curated by Barbara Cardazzo (http://pubmlst.org/aeromonas).…”
Section: The Genus Aeromonasmentioning
confidence: 99%
“…Other housekeeping genes that have been used in Aeromonas are the rpoB, which codifies for the β subunit of the RNA polymerase (Küpfer et al, 2006), the dnaJ, which codifies a thermal shock protein (Nhung et al, 2007), the recA, which codifies a protein involved in DNA repair (Sepe et al, 2008) and the cpn60, which codifies the chaperone Cpn60 type I that is involved in protein assembly (Miñana-Galbis et al, 2009). A Multilocus Phylogenetic Analysis (MLPA) of the genus Aeromonas has recently been established using the concatenated information derived from the sequences of 7 housekeeping genes: gyrB, rpoD, recA, dnaJ, gyrA, dnaX, and atpD (Martínez-Murcia et al, 2011).…”
Section: The 16s Rrna and The Housekeeping Genesmentioning
confidence: 99%
“…Nevertheless, alternative methods for species delineation, e.g. multilocus enzyme electrophoresis (MLEE) and housekeeping gene sequencing, have clarified most of the controversial taxa found in the genus Aeromonas (Miñana- Galbis et al, 2004Galbis et al, , 2009Soler et al, 2004;Nhung et al, 2007).…”
mentioning
confidence: 99%